The Effect of Disaster Education on The Ability of Adolescents to Recognize COVID-19 Prevention - Setiyawan, Setiyawan; Nugraha, Andri (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2021)
AbstractIntroduction: Disaster education to reduce disaster risk in adolescence is essential. An infectious disease that is currently spreading is covid-19. Emerging epidemiological reports of covid-19 in children show that, while they are less likely to become infected and to have the severe disease than adults, children are vulnerable to the coronavirus pandemic. Objectives: This research aimed to find out the effect of disaster education on children's ability to recognize Covid-19 prevention. Methods: This research design is quasi-experimental with a one-group pretest-posttest design approach. Disaster education intervention Covid-19 covers disaster aspects (prevention, detection, and response phases). The research instrument uses a questionnaire on students' ability to recognize covid-19 prevention. Results: Data analysis using the Wilcoxon test showed p-value of 0.000. Discussion. There is an effect of providing disaster education on children's ability to recognize covid-19 prevention. The early introduction of disaster or disease outbreaks and their prevention are the concrete means that need to be given to the younger generation to increase the children's knowledge and shape alertness behavior in dealing with the disaster or disease outbreaks.Â AbstrakPendahuluan: Pendidikan bencana untuk mengurangi risiko bencana di masa anak remaja menjadi sangat penting. Penyakit infeksius yang saat ini sedang berkembang adalah Covid-19. Laporan epidemiologis yang muncul tentang covid-19 pada anak-anak menunjukkan bahwa, sementara mereka lebih kecil kemungkinannya terinfeksi dan memiliki penyakit parah dibandingkan orang dewasa, mereka masih rentan terhadap pandemi corona virus.. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh disaster education: covid-19 terhadap kemampuan anak mengenal pencegahan covid-19. Metode: Rancangan penelitian ini adalah quasy experimental dengan pendekatan one group pretest-posttest design. Intervensi edukasi kebencanaan Covid-19 meliputi aspek kebencanaan (tahap pencegahan, deteksi dan tanggap) diberikan kepada siswa sebanyak 3 kali dengan durasi masing-masing 30 menit secara online. Instrumen penelitian menggunakan kuesioner kemampuan siswa mengenal pencegahan covid-19. Hasil: hasil analisa data dengan uji wilxocon didapatkan p-value 0.000. Diskusi : Terdapat peningkatan kemampuan siswa dalam pencegahan covid-19 setelah pemberian pendidikan bencana. Pengenalan awal bencana/ wabah penyakit dan pencegahannya merupakan media nyata yang perlu diberikan untuk para generasi muda untuk meningkatkan pengetahuan dan membentuk perilaku kesiapsiagaan dalam menghadapi bencana/ wabah